Mentor as maestro – van mineur na majeur: Die rol van oordrag tussen mentor en mentee - Nel, Johan (HTS teologiese studies, 2011)
Mentor as maestro – from minor to major: The role of transfer between mentor and mentee This article takes a glance at the role played by a mentor. The emphasis is on the authentic mentoring process. The metaphor of music is used to illustrate the different keys in which people experience life at large. The hypothesis poses that the transgression takes place during the interaction between the mentor and mentee. As in music, lives can be modulated into another, major key, which may lead to a life of abundance.